2015
DOI: 10.1126/science.aaa7017
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells generated early in life play a distinct role in maintaining self-tolerance

Abstract: Aire is an important regulator of immunological tolerance, operating in a minute subset of thymic stromal cells to induce transcripts encoding peptides that guide T-cell selection. Expression of Aire during a perinatal age-window is necessary and sufficient to prevent the multi-organ autoimmunity characteristic of Aire-deficient mice. We report that Aire promotes the perinatal generation of a distinct compartment of Foxp3+CD4+ regulatory T (Treg) cells, which stably persists in adult mice. This population has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
395
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(415 citation statements)
references
References 41 publications
15
395
0
5
Order By: Relevance
“…1B). Because it has been recently demonstrated that there are distinct Treg populations that are generated in an age-dependent manner and have different TCR repertoires (54), it might be possible that SATB1-dependent and SATB1-independent Treg cells are present. In addition to the decreased number, the suppressive functions of Treg cells were slightly impaired in the absence of SATB1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Because it has been recently demonstrated that there are distinct Treg populations that are generated in an age-dependent manner and have different TCR repertoires (54), it might be possible that SATB1-dependent and SATB1-independent Treg cells are present. In addition to the decreased number, the suppressive functions of Treg cells were slightly impaired in the absence of SATB1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] mTECs express membrane either proteins normally expressed in the thymus and proteins expressed in peripheral organs, called tissue-specific antigens (TSAs). The transcription factor autoimmune regulator (AIRE) gene (NM_000383.3), by promoting the ectopic expression of thousands of genes encoding TSAs in mTECs, plays a fundamental role in the tolerance process.…”
Section: Introductionmentioning
confidence: 99%
“…The Autoimmune Regulator ( AIRE) gene is the disease-causing gene [3,4]. AIRE acts as a transcriptional regulator and is almost exclusively expressed in the thymus [5] where it orchestrates the process of negative selection of self-reactive T cells and contributes to the development of regulatory T cells (Tregs) [6,7]. All patients present autoantibodies against autoantigens expressed in the affected tissue [8] and/or against immune mediators such as interferon-omega (ω) and interleukin (IL)-22 [9,10].…”
mentioning
confidence: 99%